Regulation of crucial lncRNAs in differentiation of chicken embryonic stem cells to spermatogonia stem cells. (14th November 2016) - Li, D.; Ji, Y.; Wang, F.; Wang, Y.; Wang, M.; Zhang, C.; Zhang, W.; Lu, Z.; Sun, C.; Ahmed, M. F.; He, N.; Jin, K.; et al.
Summary: Regulation of crucial lncRNAs involved in differentiation of chicken embryonic stem cells (ESCs) to spermatogonia stem cells (SSCs) was explored by sequencing the transcriptome of ESCs, primordial germ cells (PGCs) and SSCs with RNA‐Seq; analytical bioinformatic methods were used to excavate candidate lncRNAs. We detected expression of candidate lncRNAs in ESCs, PGCs and SSCs and forecasted related target genes. Utilizingwego, david andstring, function and protein–protein interactions of target genes were analyzed. Finally, based onstring analysis, interaction diagrams and relevant signaling pathways were established. Our results indicate a total of 9657 lncRNAs in ESCs, PGCs and SSCs, with 3549 defined as significantly different. We screened 20 candidate lncRNAs, each demonstrating a greater than eight‐fold difference in |logFC| value between groups (ESCs vs. PGCs, ESCs vs. SSCs and PGCs vs. SSCs) or specifically expressed in an individual cell type. qRT‐PCR results indicated that expression tendencies of candidate lncRNAs were consistent with RNA‐Seq. Fifteen cis and four trans target genes were forecasted. Based onwego andstring analyses, we found lnc‐SSC1, lnc‐SSC5, lnc‐SSC2 and lnc‐ESC2 negatively regulated target genes SUFU, EPHA3, KLF3, ARL3 and TRIM8, whereas SHH, NOTCH, TGF‐ β, cAMP/cGMP and JAK/STAT signaling pathways were promoted, causing differentiation of ESCs into SSCs. Our findings represent a preliminary unveiling of lncRNA‐associated regulatory mechanisms during differentiation of chicken ESCs into SSCs, filling a research void in male germ cell differentiation related to lncRNA. Our results also provide basic information for improving in vitro induction systems for differentiation of chicken ESCs into SSCs.